The Urgency of Good Corporate Governance in The Per-spective of Business Law in Indonesia - Ashuri Ashuri; Nandang Sambas (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
The implementation of Good Corporate Governance (GCG) principles in business practices in Indonesia has a high urgency to create a healthy, transparent and equitable business climate. This article examines the importance of GCG implementation from the perspective of business law, by highlighting the various challenges faced by business actors in implementing the principles of transparency, accountability, responsibility, independence, and fairness. The study also analyzes the role of regulation and law enforcement in strengthening GCG practices and their impact on investor protection and business continuity. Using a juristic normative approach, this article emphasizes that GCG is not only an ethical instrument, but also a legal obligation that supports the creation of sustainable and highly competitive corporate governance at the national and global levels.